Multifunctional transcription factor CytR of Vibrio cholerae is important for pathogenesis. Issue 12 (4th December 2020) - Das, Suman; Chourashi, Rhishita; Mukherjee, Priyadarshini; Gope, Animesh; Koley, Hemanta; Dutta, Moumita; Mukhopadhyay, Asish K.; Okamoto, Keinosuke; Chatterjee, Nabendu Sekhar
Abstract : Vibrio cholerae, the Gram-negative facultative pathogen, resides in the aquatic environment and infects humans and causes diarrhoeagenic cholera. Although the environment differs drastically, V. cholerae thrives in both of these conditions aptly and chitinases play a vital role in their persistence and nutrient acquisition. Chitinases also play a role in V. cholerae pathogenesis. Chitinases and its downstream chitin utilization genes are regulated by sensor histidine kinase ChiS, which also plays a significant role in pathogenesis. Recent exploration suggests that CytR, a transcription factor of the LacI family in V. cholerae, also regulates chitinase secretion in environmental conditions. Since chitinases and chitinase regulator ChiS is involved in pathogenesis, CytR might also play a significant role in pathogenicity. However, the role of CytR in pathogenesis is yet to be known. This study explores the regulation of CytR on the activation of ChiS in the presence of mucin and its role in pathogenesis. Therefore, we created a CytR isogenic mutant strain of V. cholerae (CytR¯) and found considerably less β-hexosaminidase enzyme production, which is an indicator of ChiS activity. The CytR¯ strain greatly reduced the expression of chitinases chiA1 and chiA2 in mucin-supplemented media. Electron microscopy showed that the CytR¯ strain was aflagellate. The expression of flagellar-synthesis regulatory genes flrB, flrC and class III flagellar-synthesis genes were reduced in the CytR¯ strain. The isogenic CytR mutant showed less growth compared to the wild-type in mucin-supplemented media as well as demonstrated highly retarded motility and reduced mucin-layer penetration. The CytR mutant revealed decreased adherence to the HT-29 cell line. In animal models, reduced fluid accumulation and colonization were observed during infection with the CytR¯ strain due to reduced expression of ctxB, toxT and tcpA . Collectively these data suggest that CytR plays an important role in V. cholerae pathogenesis.